TRUTH AS A FACTOR OF SUCCESS IN LIFE: LEONAS JOVAIŠA’S POINT OF VIEW - Tijūnėlienė, Ona (Acta Paedagogica Vilnensia, 2010)
In the context of globalization it is not easy to make one’s own life successful: people experience crisis of values and ideals. Outstanding Lithuanian educologist L.Jovai a states that success or lack of it in life is not an accidental thing. Success is manageable. The basis of its management is conscious building of success in life. The article discusses L. Jovai a’s view on truth and its relationship with success in life Truth as factor of success in life is analysed. The following essential ideas were disclosed: 1) The human being is the final source of information that ensures the relationships, development, and the harmony of the existence. The philosophy of harmony directs to the understanding of the state of existence and the fact that wisdom is a necessity, as it means harmony. Wisdom covers global justice and morals caused by harmony – love. 2) Man is part of the being, information ally of body and spirit. Inner harmony of a free individual, harmony with the being and existence, and wise life is the supreme good of education, the supreme state, and the supreme meaning. The information presented to an individual should aim to disclose the truth about the fundamentals of the universe, and the structure and the fate of human existence. 3) The integral basis of man‘s social life is self-expression in man‘s interaction with the environment. Real life means the direct relationship of daily activity with a long-term or an eternal, global aim.